Coleopterofauna visitante de Theobroma grandiflorum Schum. (Sterculiaceae) de uma plantação nos arredores de Manaus, Amazonas, Brasil1 - Barbosa, Maria das Graças Vale; Fonseca, Claudio Ruy Vasconcelos da (Acta Amazonica, 2002)
The cupuassu (Theobroma grandiflorum, Sterculiaceae) is a native Amazonian fruit tree that about its entomological informations had been demonstrated the highest insects diversity princi-pallyColeoptera. During in a period of 12 consecutive months, manual collections were realized using insecticide and flight interception traps in a private plantation of cupuassu in Manaus and 1.212 individuals of Coleoptera visitors of Theobroma grandiflorum were collected Some plants aspects phenologies were done. The most great abundance was registered in plants exposed to the sun, in plants with flowers and without fruits, and plants localized in level and steep areas. Seasonal differences were also considered, finding a greater frequency of samples in the months corresponding to the less rainy period (from June to November). The quantity of samples collected (and the families of Coleoptera) was correlated with the period of collection, the morning hours presenting a greater sample quantity. From the Coleoptera found visiting the cupuassu plants, 32 families were collected and identified, the most abundant of which were Chrysomelidae 25.17%, Curculionidae 18.08%, Staphylinidae 17,57%, Coccinellidae 12.46%. The species Homophoeta aequinoctialis, Exora obsoleta, Spaethiella coccinea (Chrysomelidae). Colobothea hirtipes, Clorida curta,Compsibidion maronicum, Heterachthes pelonioides (Cereambycidae) and Marshallius multisignatus (Curculionidae), were identified. The samples of Desmobaris and Heilipus were found on leaves spronts and flowers of the plants being considered pest of young cupuassu plants, (Phytotribus), however their relation with the plant is not know yet. The Spaethiella coccinea (Chrysomelidae, Hispinae) was observed and collected feeding on leaves of the cupuassu plant.
Fauna of coleoptera on Theobroma grandiflorum Schum. (Sterculiaceae) in Manaus, Amazonas state, Brazil
Keywords: Coleoptera; Theobroma Grandiflorum; Cupuassu; Amazon; Coleoptera; Theobroma Grandiflorum; Método De Queda; Armadilhas De Interceptação De Vôo; Amazônia